Alternative Pathways in the Pathophysiology of Priapism - Karakeci, Ahmet (Fırat University, 2014)
Priapism is described as the extended unpreferred erection status without any sexual stimulus. There are three types of priapism which are classified as ischemic, non ischemic and recurrent priapism depending on the blood flow of the penile artery. Ischemic priapism is a real urological emergency which requires urgent and appropriate approach. Recently, it was shown in experimental priapism models that adenosine and hemoxygenase-1-carbonmonoxide (HO1-CO) are effective in the development of recurrent priapism attacks. Moreover, it was reported that dysregulated PDE-5 activity, decreased Norepinephrine response and altered Endothelin receptor activity may be effective in the pathophysiology of priapism. In the present study, the experimental data related to the pathways that play an active role in the pathophysiology of priapism and its reflections on the practice were evaluated.

Priapizm, cinsel uyarı olmaksızın uzamış istenmeyen ereksiyon halidir. Priapizmin penil arter kan akımına bağlı olarak iskemik, non iskemik ve tekrarlayan olmak üzere üç tipi vardır. İskemik priapizm hızlı ve doğru yaklaşım gerektiren gerçek ürolojik bir acildir. Son yıllarda özellikle adenozin ve hemoksijenaz 1-karbonmonoksit'in tekrarlayan priapizm ataklarında etkin olduğu deneysel modellerde belirlenmiştir. Ayrıca priapizm patofizyolojisinde disregüle PDE5 aktivitesi, azalmış Norepinefrin cevabı ve Endotelin-1'in değişen reseptör aktivitesinin de etkin olabileceği bildirilmektedir. Bu çalışmada, priapizm patofizyolojisinde etkin rol oynayan yolaklarla ilgili deneysel veriler ve klinik yansımaları değerlendirildi.
Priapizm Patofizyolojisinde Alternatif Yolaklar